Expression patterns of claudins in patients with triple‐negative breast cancer are associated with nodal metastasis and worse outcome. Issue 8 (11th July 2017) - Katayama, Ayaka; Handa, Tadashi; Komatsu, Kei; Togo, Maria; Horiguchi, Jun; Nishiyama, Masahiko; Oyama, Tetsunari
Abstract : Claudins (CLDNs) are key cell adhesion molecules, which compose tight junctions (TJs), and the disruption of TJs is associated with cancer development. Here we immunohistochemically studied expression patterns of CLDNs in 222 primary invasive breast cancers including 68 triple‐negative breast cancers (TNBCs), and examined their correlation with epithelial‐to‐mesenchymal transition (EMT)‐related markers, breast cancer stem cell (BCSC) markers, and clinicopathological features including patients' clinical outcome. Tumor margins were classified as three infiltrating growth patterns (expanding, intermediate and infiltrating). For CLDN1, 3, 4, and 7, their expression rates were more frequent in TNBCs than in other subtypes (11.8% vs 0.7%, 26.5% vs 2.0%, 48.5% vs 11.1%, and 32.4% vs 8.7%, respectively; P ≤ 0.001). In 68 TNBCs, we identified high Ki67 labeling index (LI) and the combination of CLDN4 high/CLDN7 low expression as independent predictors of axillary nodal metastasis ( P = 0.019; OR, 4.36; 95%CI, 1.28–14.90 and P = 0.007; OR, 5.33; 95%CI, 1.58–17.90). Moreover, the combination of CLDN1 low/CLDN7 low/E‐cadherin negative as well as tumor infiltrating patterns were predictors for worse recurrence‐free survival by univariate analyses in TNBCs ( P = 0.005 and P = 0.011). Our analyses provide further evidence that CLDNs would be valuable prognostic markers in TNBCs.